RANCANG BANGUN APLIKASI SURVEY ONLINE UNTUK MENDUKUNG PROSES AKREDITASI DAN PENYUSUNAN KURIKULUM 2013 MENGGUNAKAN GOOGLE DOCUMENTS - Jauhari, Mochammad Helmi; Sulaksono, Juli (Universitas Nusantara PGRI Kediri, 2014)
Online surveys is one of theinstruments used to obtain the actualdata with the specific purpose over heinternet. A survey of students, faculty,alumni and stakeholders becomes veryimportant requirement for being a majorsource of data in the accreditationprocess and the preparation ofcurriculum 2013.The purpose of this research is todesign and build applications onlinesurvey to students, alumni, faculty andstakeholders associated with the datarequired in the process of accreditationof courses and institutions.The application engineeringprocess based on software engineeringtheory that is supported by a web-basedservice google documents. Utilizationgoogle documents is done withconsideration of the safety factor, theavailability of storage space, continuityof data and ease of access by the user.This research will be conductedusing a reference obtained from theliterature on web-based software and usegoogle documents to the onlineapplication form with supportingdocuments containing guidelines for theaccreditation of study programs as wellas books curriculum guide 2013.The benefits obtained with thisapplication is to facilitate the capture,storage, security, and data analysis ofstudents, alumni, faculty andstakeholders in supporting the process ofaccreditation and curriculumdevelopment in 2013 at the University ofPGRI Nusantara Kediri. Keywords: design, onlinesurveys, accreditation, curriculum, 2013,google documents.